2001
DOI: 10.1046/j.1365-2656.2001.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting breeding dispersal in the facultatively colonial lesser kestrel: individual experience vs. conspecific cues

Abstract: Summary1. The role of individual experience vs. the use of conspecific cues on breeding dispersal decisions have seldom been determined in colonial birds. We studied causes of breeding dispersal in the lesser kestrel ( Falco naumanni ), a species that breeds in colonies of variable size as well as solitarily. During a 6-year study in Spain, we gathered information on 486 subsequent breeding attempts and on 26 explanatory variables which evaluated individual experience, conspecific cues in terms of breeding per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
186
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(202 citation statements)
references
References 64 publications
(145 reference statements)
11
186
1
2
Order By: Relevance
“…Other factors potentially related to the social constraints hypothesis, such as individual quality and age, were not assessed. The importance of individual quality (other than age) for breeding dispersal has generally received little attention, whereas age-related effects on breeding dispersal were found in some studies (Pärt and Gustafsson 1989;Payne and Payne 1993;Daniels and Walters 2000;Newton 2001;Blakesley et al 2006), but not in others (Forero et al 1999;Serrano et al 2001;Hoover 2003;Sedgwick 2004). …”
Section: Social Constraintsmentioning
confidence: 99%
“…Other factors potentially related to the social constraints hypothesis, such as individual quality and age, were not assessed. The importance of individual quality (other than age) for breeding dispersal has generally received little attention, whereas age-related effects on breeding dispersal were found in some studies (Pärt and Gustafsson 1989;Payne and Payne 1993;Daniels and Walters 2000;Newton 2001;Blakesley et al 2006), but not in others (Forero et al 1999;Serrano et al 2001;Hoover 2003;Sedgwick 2004). …”
Section: Social Constraintsmentioning
confidence: 99%
“…Further benefits of living in large colonies include the reduced risk of predation for adults and their offspring and the reduction of individual investment in vigilance . Moreover, colony size regulates the dispersal of lesser kestrels, which use the number of conspecifics as a cue to colony quality and tend to move to large colonies (Serrano et al, 2001;Serrano and Tella, 2003). Earlier studies found colony size to be positively associated with reproductive success in this species (Serrano and Tella, 2007), and nestling survival was higher in large colonies (Serrano et al, 2001), due to the interaction between nest distance and breeder abundance (Di Maggio et al, 2013).…”
Section: Effect Of Colony Size On Lesser Kestrel Demographymentioning
confidence: 98%
“…The low breeding dispersal is congruent with findings in other populations (cf. Serrano et al, 2001 in which 71.6% of breeding lesser kestrels were recruited into the same colony or settled in colonies within their previous foraging habitats). Moreover, no cases of adult emigration to neighboring populations were detected during the study period, in spite of specific monitoring of the colonies outside the Gela Plain.…”
Section: Survival and Recapture Probabilitiesmentioning
confidence: 99%
“…Juveniles that dispersed did so on long distances, while adults showed much higher fidelity on their breeding grounds. There is evidence that the probability of dispersal decreases with age (Serrano et al 2001, Calabuig et al 2008 while such long distance dispersal movements exist but could be underestimated (Prugnolle et al 2003). A reason for that could be that estimating philopatry rates from ringing recovery data has its drawbacks since ringing intensity varies with locations and longdistance dispersal movements of individuals could be difficult to detect.…”
Section: Philopatrymentioning
confidence: 99%